10 Cell-Permeable Cyclic AMP as a Novel Cardioprotective Agent. (19th January 2014) - Dudley, D J; Suleiman, M S; Bond, M; James, A F; Khaliulin, I
Abstract : We have recently shown that consecutive heart perfusion with isoproterenol and adenosine strongly protects the heart against ischaemia/reperfusion injury. Isoproterenol activates β-adrenergic receptors increasing synthesis of cyclic AMP (cAMP) which in turn activates both protein kinase A (PKA) and a guanine nucleotide exchange factor- Epac- whilst adenosine activates protein kinase C. However, this treatment may not be effective if β-adrenergic sensitivity is impaired by some pathological conditions. We decided to check whether a cardioprotective effect can be achieved by direct activation of PKA and Epac using a cell-permeable cAMP analogue 8-Br-cAMP-AM. Isolated rat hearts were perfused with 1 μM 8-Br-cAMP-AM for 5 min followed by 5 min washout period prior to 30 min ischaemia and 2 h reperfusion. 8-Br-cAMP-AM itself did not change haemodynamic function but resulted in decreased function during the washout period prior to ischaemia and significantly reduced amplitude of ischaemic contracture. During reperfusion, the cell-permeable cAMP analogue decreased end diastolic pressure, lactate dehydrogenase release and infarct size and considerably improved haemodynamic functional recovery. These results demonstrate that the cell permeable cAMP analogue 8-Br-cAMP-AM, at a relatively low dose, can induce cardioprotective effect directly, without β-adrenergic stimulation. This could be the way to activate survival signal transduction pathways if β-adrenergic receptor sensitivity is impaired. Further study is needed in order to elucidate the signalling mechanisms of this protective effect and to optimise this intervention. Supported by the BHF.